Selling the Safe City? The Politics of Certification and the case of Purple Flag Sweden - Brandén, Jennie; Rönnblom, Malin (Scandinavian Journal of Public Administration, 2019)
In recent years, bureaucratic and market-based tools such as certifications have become common tools for addressing complex, gendered and power-related issues such as discrimination, gender equality and, in this case, safety. Drawing on a discursive understanding of policy and politics, this paper examines how safety in public space is being addressed and given meaning in nine Swedish cities, working with a safetycertification entitled ‘the Purple Flag’. Our analysis shows that in the work with PurpleFlag, safety is represented as a technical problem, requiring a standardised method, and as a tool for growth, focusing on the commercial potential of safety for the city. These representations position the safety worker as mainly administrative and competitive, while the recipients of safety become visitors and consumers. Purple Flag also gears local safety measures towards urban business areas, rather than towards places with high levels of crime or unsafety, and primarily target those disturbing the order of the market in the city centre as problematic. Our conclusion is that the method of certification creates major difficulties for politicising safety and instead enables an “economisation of the political”,producing safety for the urban market rather than for urban citizens.